Vitamin C attenuates methotrexate-induced oxidative stress in kidney and liver of rats - Savran, M.; Cicek, E.; Doguc, D. K.; Asci, H.; Yesilot, S.; Candan, I. A.; Ozer, M. K. (Akademiai Kiado Zrt, 2017)
Like several other anticancer drugs, methotrexate (MTX) causes side effects, such as neuropathic pain, hepatotoxicity, and nephrotoxicity. Abnormal production of reactive oxygen species has been suspected in the pathophysiology of MTX-induced hepatorenal toxicity. Therefore, the aim of this study was to investigate the probable protective role of vitamin C (Vit C) on oxidative stress induced by MTX in the liver and kidney tissues of rats. A total of 32 rats were randomly and equally divided into four groups. The first group served as the control group. The second group received a single dose of 20 mg/kg of MTX intraperitoneally. To demonstrate our hypothesis, the third and the fourth groups received 250 mg/kg of Vit C for 3 days by oral gavage, with or without MTX treatment. At the end of the study, the liver and kidney tissues of the rats were collected and examined using histology. Both the tissues were assayed for malondialdehyde concentration and superoxide dismutase (SOD), catalase (CAT), and glutathione peroxidase (GSH-Px) activities. In hepatic and renal tissues, lipid peroxidation levels were increased, whereas SOD, CAT, and GSH-Px levels were decreased by MTX. All parameters, including CAT levels in hepatic tissue, were significantly restored after the administration of Vit C for 3 days. Similar to the biochemical findings, evidence of oxidative damage was examined in both types of tissues by histopathological examination. From the results of this study, we were able to observe that Vit C administration modulates the antioxidant redox system and reduces the renal and hepatic oxidative stress induced by MTX. Vit C can ameliorate the toxic effect of MTX in liver and kidney tissues of rat.
Keywords: methotrexate; vitamin C; kidney; liver; oxidative stress